Complex Interactions between Fungal Avirulence Genes and Their Corresponding Plant Resistance Genes and Consequences for Disease Resistance Management - Petit-Houdenot, Yohann; Fudal, Isabelle (Frontiers in Plant Science, 2017)
During infection, pathogens secrete an arsenal of molecules, collectively called effectors, key elements of pathogenesis which modulate innate immunity of the plant and facilitate infection. Some of these effectors can be recognized directly or indirectly by resistance (R) proteins from the plant and are then called avirulence (AVR) proteins. This recognition usually triggers defense responses including the hypersensitive response and results in resistance of the plant. R - AVR gene interactions are frequently exploited in the field to control diseases. Recently, the availability of fungal genomes has accelerated the identification of AVR genes in plant pathogenic fungi, including in fungi infecting agronomically important crops. While single AVR genes recognized by their corresponding R gene were identified, more and more complex interactions between AVR and R genes are reported (e.g. AVR genes recognized by several R genes, R genes recognizing several AVR genes in distinct organisms, one AVR gene suppressing recognition of another AVR gene by its corresponding R gene, two cooperating R genes both necessary to recognize an AVR gene). These complex interactions were particularly reported in pathosystems showing a long co-evolution with their host plant but could also result from the way agronomic crops were obtained and improved (e.g. through interspecific hybridization or introgression of resistance genes from wild related species into cultivated crops). In this review, we describe some complex R - AVR interactions between plants and fungi that were recently reported and discuss their implications for AVR gene evolution and R gene management.